In Vitro Comparison of Two Barbed Suture Configurations for Flexor Tendon Repair - Engel, Jamie L.; Gabra, Joseph N.; Esterle, Andrew R.; Lanzinger, William D.; Elias, John J. (Journal of Hand and Microsurgery, 2017)
Purpose The current study compares the strength of a previously studied technique for flexor tendon repair with barbed sutures to an experimental approach that aligns all the barbs to oppose distraction.Methods Twelve flexor tendons from cadaveric specimens were mechanically tested following repair of simulated zone II tendon injuries. Two repair techniques utilizing barbed sutures were studied: the Marrero-Amadeo four-core barbed suture approach and the experimental configuration with all barbs on four cores opposing distraction. Maximum applied load at failure, that is, ultimate load, and 2-mm gap force were compared between the two repair techniques, both as raw values and after normalization to cross-sectional area of the intact tendon. Statistical testing was performed using t-tests and Mann-Whitney U-tests, where appropriate, with a significance level of 0.05.Results The ultimate loads, raw (58.2 N) and normalized (4.8 N/mm2), were significantly larger for the Marrero-Amadeo repair than the proposed experimental approach (35.6 N and 2.7 N/mm2; p < 0.05). No significant differences were identified for 2-mm gap force.Conclusion The innovation of suturing to align all barbs to oppose distraction does not improve strength of the repaired tendon. The Marrero-Amadeo technique was found to have superior strength for use in traumatic zone II flexor tendon injuries.
Keywords: flexor tendon repair; barbed suture; strength; mechanical testing